Modularization and Serialization Design Method of Yaw Planetary Reducer - Dong Huimin; Xu Wenhui; Zhang Xinhua; Wang Delun; Bao Yanqiu; Qiu Jun (Jixie chuandong)
The modularization and serialization design idea is introduced into the method to research the design method of yaw reducer of wind power transmission system,a new configuration programs- NGW compound NGWN（ Ⅰ） is proposed,serialization basic planetary gear transmission modules are formed,the parts reusability and interchangeability of yawing reducer are enhanced. According to the definition of modular design approach,the yawing reducer planetary transmission mechanism is divided into NGW type and NGWN（ Ⅰ）type two planetary modules. The tooth number optimization model is built for both modules respectively,the same type and function but different transmission ratio planetary planets modules are formed,there are 28 species NGW modules and 9 species NGWN（ Ⅰ） modules. By the definition of serialization design method,the standard series modulus are given,the gear module series are formed. Finally,the wind power yaw reducer rapid design process is established based on planetary modules. The reference to design yaw planetary reducer in wind power transmission system is provided.